Predictors of the risk of falls among elderly with chronic atrial fibrillation (Clinics, 2012)
OBJECTIVES: Though elderly persons with chronic atrial fibrillation have more comorbidities that could limit indications for the chronic use of anticoagulants, few studies have focused on the risk of falls within this particular group. To evaluate the predictors of the risk of falls among elderly with chronic atrial fibrillation, a cross-sectional, observational study was performed. METHODS: From 295 consecutive patients aged 60 years or older with a history of atrial fibrillation who were enrolled within the last 2 years in the cardiogeriatrics outpatient clinic of the Instituto do Coração do Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 107 took part in this study. Their age was 77.9±6.4 years, and 62 were female. They were divided into two groups: a) no history of falls in the previous year and b) a history of one or more falls in the previous year. Data regarding the history of falls and social, demographic, anthropometric, and clinical information were collected. Multidimensional assessment instruments and questionnaires were applied. RESULTS: At least one fall was reported in 55 patients (51.4%). Among them, 27 (49.1%) presented recurrent falls, with body lesions in 90.4% and fractures in 9.1% of the cases. Multivariate logistic regression showed that selfreported difficulty maintaining balance, use of amiodarone, and diabetes were independent variables associated with the risk of falls, with a sensitivity of 92.9% and a specificity of 44.9%. CONCLUSION: In a group of elderly patients with chronic atrial fibrillation who were relatively independent and able to attend an outpatient clinic, the occurrence of falls with recurrence and clinical consequences was high. Difficulty maintaining balance, the use of amiodarone and a diagnosis of diabetes mellitus were independent predictors of the risk for falls. Thus, simple clinical data predicted falls better than objective functional tests.